2014
DOI: 10.1002/cne.23556
|View full text |Cite
|
Sign up to set email alerts
|

Cortical hypoplasia and ventriculomegaly of p73‐deficient mice: Developmental and adult analysis

Abstract: Trp73, a member of the p53 gene family, plays a crucial role in neural development. We describe two main phenotypic variants of p73 deficiency in the brain, a severe one characterized by massive apoptosis in the cortex leading to early postnatal death and a milder, non-/low-apoptosis one in which 50% of pups may reach adulthood using an intensive-care breeding protocol. Both variants display the core triad of p73 deficiency: cortical hypoplasia, hippocampal malformations, and ventriculomegaly. We studied the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 48 publications
3
30
0
2
Order By: Relevance
“…We also noted a lack of MCCs in the ependymal cells (data not shown). It was recently reported that p73 is strongly expressed in murine ciliated ependymal cells and is required for their survival (Medina-Bolivar et al, 2014). p73 protein expression appeared nuclear by IF and was detected in the epithelium of *α-tubulin-positive tissues in p73+/+ animals (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…We also noted a lack of MCCs in the ependymal cells (data not shown). It was recently reported that p73 is strongly expressed in murine ciliated ependymal cells and is required for their survival (Medina-Bolivar et al, 2014). p73 protein expression appeared nuclear by IF and was detected in the epithelium of *α-tubulin-positive tissues in p73+/+ animals (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…; Medina‐Bolívar et al. ). While the p73KO neocortex has a variety of rather mild anatomical defects and an important hydrocephaly, the dominant malformation is the severe hippocampal dysgenesis.…”
Section: Introductionmentioning
confidence: 98%
“…in brain development (Meyer, ; Medina‐Bolívar et al. ; Niklison‐Chirou et al. ), ciliogenesis (Nemajerova et al.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is thought to be caused by an unspecified immune defect (Yang et al 2000). Interestingly, multiciliated ependymal cells that line ventricles and generate cerebrospinal fluid flow express p73, and p73 knockout ependyma displays impaired ciliogenesis (Medina-Bolivar et al 2014;Gonzalez-Cano et al 2015). While p73 knockout mice have severe hydrocephalus, isoform-specific knockout brains show milder discrete cortical phenotypes (Yang et al 2000;Tomasini et al 2008;Tissir et al 2009).…”
mentioning
confidence: 99%